Therapy adherence in community elderly from inner and coast councils of Northern Portugal - Pinto, Isabel C. (2018)
Global aging associated with chronic comorbidities leads to increased simultaneous use of drugs and complex drug therapies. Therapy adherence is essential to ensure the effectiveness of therapeutic and control of chronic diseases in elderly. Objectives: To estimate the prevalence of therapy adherence and associated factors in community elderly from inner and coast councils of northern Portugal. Methods: This cross-sectional and correlational study was based on a questionnaire, with MAT scale (measure of adherence to therapy) validated for the Portuguese population (Delgado & Lima, 2001), applied by interview to 384 elderly (≥65 years) living in the community in northern Portugal councils of Esposende, Guimarães and Lamego. It was used descriptive statistics and Chi-Square test, with a significance level of 5%. Results: The sample consisted mainly of females elderly (60,7%), with age mean of 75.8 years old, while 47.7% was between 65-74 years. On average, 4.99 different drugs are administered per day, being medicines that act on the circulatory system the most prescribed. The prevalence of therapy adherence was 86,6%. Elderly people who have help with medication, are those who most adhere to drug therapy (p=0.035). Conclusions: This study shows a considerable prevalence of therapy adherence. Having help with medication seems to be associated with better therapy adherence.